Possibility of the application of the computational intelligence in the production of superhard materials. Report 2 - Tavares, L.O.; Vianna, W.S.; Bobrovnitchii, G.S.; Skury, A.L.D.; Rangel, J.J.A. (Сверхтвердые материалы, 2012)
A new system to control a 630-ton and a 2500-ton presses has been developed. By using this system it has been made possible to define new parameters related to pressure and temperature and the influence of certain factors on them. Furthermore, the new system has been shown to indicate that other parameters, such as height of the gasket formed, electrical resistance of the reaction cell, and the frequency of activation of the pump or multiplier, can serve as important indicators of the improvement of superhard material production technologies, implementing the Computational Intelligence. Розроблено нову систему управління пресами зусиллям 630 і 2500 тонн. За допомогою цієї системи стало можливим визначити нові параметри, що пов’язані з тиском і температурою, і вплив на них певних факторів. Крім того, інші параметри, такі як висота ущільнення, що утворюється, електричний опір реакційної комірки і частота активації насоса або мультиплікатора, можуть бути важливими показниками удосконалення технології отримання надтвердих матеріалів при використанні обчислювального інтелекту. Разработана новая система управления прессами усилием 630 и 2500 тонн. С помощью этой системы стало возможным определить новые параметры, связанные с давлением и температурой, и влияние на них определенных факторов. Кроме того, другие параметры, такие как высота образующегося уплотнения, электросопротивление реакционной ячейки и частота активации насоса или мультипликатора, могут служить важными показателями улучшения технологии получения сверхтвердых материалов, используя вычислительный интеллект.